2021
DOI: 10.1038/s41598-021-02892-x
|View full text |Cite
|
Sign up to set email alerts
|

Determining and quantifying the historical traces of spatial land arrangements in rural landscapes of Central and Eastern Europe

Abstract: The article attempts to define and determine the intangible components of cultural heritage related to the spatial structure of land in a comprehensive way using computational methods. The components were quantified and a method of empirical evaluation of landscape durability was proposed for agricultural areas of significant cultural and historical value with an evident mosaic structure of fields, baulks, ponds, meadows, and forests. This method allows us to identify places more resistant to political transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…In the aggregation calculation stage after ranking, the Hard Mathematical method selects the optimal result by calculating the sum and average of the values (or scores) of all or specific alternatives. Based on the Hard Mathematical method, the Soft Mathematical method adds the human intervention of decision makers, and is used to solve the research problems of public participation [ 108 , 128 , 146 , 147 ] and conflicts of views [ 86 , 126 , 138 , 152 ]. The voting method determines the optimal result by selecting a number of stakeholders involved in the research problem to vote on the alternatives, and is mainly used to solve research problems of public participation and community co-governance [ 93 , 122 , 145 , 157 ].…”
Section: Detail Review Analysis and Resultsmentioning
confidence: 99%
“…In the aggregation calculation stage after ranking, the Hard Mathematical method selects the optimal result by calculating the sum and average of the values (or scores) of all or specific alternatives. Based on the Hard Mathematical method, the Soft Mathematical method adds the human intervention of decision makers, and is used to solve the research problems of public participation [ 108 , 128 , 146 , 147 ] and conflicts of views [ 86 , 126 , 138 , 152 ]. The voting method determines the optimal result by selecting a number of stakeholders involved in the research problem to vote on the alternatives, and is mainly used to solve research problems of public participation and community co-governance [ 93 , 122 , 145 , 157 ].…”
Section: Detail Review Analysis and Resultsmentioning
confidence: 99%
“…Being an important part of the functioning of rural areas, cultural identity, together with cultural spaces in cities and suburbs, can be preserved and promoted through an effort to protect cultural heritage [69]. Research confirmed the significant contribution of cultural and environmental heritage to economic growth, social inclusion, and environmental sustainability in rural areas, indicating culture as the fourth pillar of sustainable development [70].…”
Section: Is Cultural Heritage Actually Vanishing?mentioning
confidence: 90%
“…Structural transformations in rural space cause irreversible changes. Preservation and protection of cultural heritage components, also those related to the spatial structure of the land, may alleviate the adverse impact of development pressure [69].…”
Section: Is Cultural Heritage Actually Vanishing?mentioning
confidence: 99%
“…Cultural heritage is most commonly considered from the perspective of tangible, intangible and environmental assets, but technological and socioeconomic changes yielded a new category, digital heritage. This category is relevant to rural areas as well, even though they used to be associated with cultural landscapes (Soloviy et al, 2021. Prus et al, 2021, tangible heritage, such as religious artefacts and handicraft (Fonseca and Ramos, 2012), traditional architecture and land (Olczak et al, 2022), and nontangible heritage (George, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This category is relevant to rural areas as well, even though they used to be associated with cultural landscapes (Soloviy et al , 2021. Prus et al , 2021), tangible heritage, such as religious artefacts and handicraft (Fonseca and Ramos, 2012), traditional architecture and land (Olczak et al , 2022), and nontangible heritage (George, 2010). Digital heritage, on the other hand, is more likely to bring to mind the digitalisation of analogue collections.…”
Section: Introductionmentioning
confidence: 99%